Penanaman Sikap Sosial Anti Perundungan Verbal Melalui Pembelajaran IPS Kelas VII Pada Materi Sosialisasi, Nilai dan Norma - Dewi Pramudita Maryudi; Ikfi Khoulita (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to examine the phenomenon of cultivating anti-verbal bullying social attitudes through 7th-grade Social Studies (IPS) education focusing on socialization, values, and norms. Verbal bullying is a serious issue in schools that negatively impacts victims. The study employs a qualitative approach using a case study method. Primary data was gathered through observations and interviews at SMPN 3 Srengat, while secondary data came from literature reviews. The research findings indicate two main patterns in cultivating anti-verbal bullying social attitudes: habituation patterns and modeling patterns. Habituation involves providing advice, motivation, and exemplary behavior to students. Modeling is done by presenting real, symbolic, and dual examples to students. Both patterns have challenges and room for improvement. Teachers need to be consistent in applying habituation and modeling patterns, while also considering factors that may cause verbal bullying. This research contributes to understanding the phenomenon of verbal bullying in schools and offers strategies for instilling anti-verbal bullying social attitudes through IPS education.